Inculturation: Adaptation, innovation and reflexivity an African Christian perspective - Duncan, Graham (HTS teologiese studies, 2014)
The purpose of this article is to examine the changing understandings of processes and terms which have been and are currently in use regarding the outworking of the mission of the church. This historical and missiological approach will evaluate the contribution of a number of African and other theologians during the 20th century and also the opening years of the 21st century. It will cover the missionary period from the end of the 18th century with a special focus on the impact during the ‘high missionary era’ (1880–1920) to the present. The focus will predominantly be on Africa and Pentecostalism, the role of women and the African diaspora as examples of effective inculturation.